2002
DOI: 10.1017/s0022029901005258
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high intensity pulsed electric fields and heat treatments on vitamins of milk

Abstract: S. The effects of high intensity pulsed electric field (HIPEF) treatments at room or moderate temperature on water-soluble (thiamine, riboflavin, ascorbic acid) and fat-soluble vitamins (cholecalciferol and tocopherol) were evaluated and compared with conventional thermal treatments. Vitamin retention was determined in two different substrates, milk and simulated skim milk ultrafiltrate (SMUF). Samples were subjected to HIPEF treatments of up to 400 µs at field strengths from 18n3 to 27n1 kV\cm and to he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
0
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(63 citation statements)
references
References 10 publications
4
57
0
2
Order By: Relevance
“…Several authors have studied the evolution of ascorbic acid in citrus juices or milk after PEF or heat treatment (Bendicho, Espachs, Arántegui, & Martín, 2002;Polydera, Stoforos, & Taoukis, 2003;Torregrosa, Esteve, Frígola, & Cortés, 2006;Yeom, Streaker, Zhang, & Min, 2000), however, no similar studies have been found in more complex matrices such as orange juice-milk beverages. Therefore, the objective of the present work was to study the ascorbic acid degradation in a PEF-treated orange juice-milk beverage.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have studied the evolution of ascorbic acid in citrus juices or milk after PEF or heat treatment (Bendicho, Espachs, Arántegui, & Martín, 2002;Polydera, Stoforos, & Taoukis, 2003;Torregrosa, Esteve, Frígola, & Cortés, 2006;Yeom, Streaker, Zhang, & Min, 2000), however, no similar studies have been found in more complex matrices such as orange juice-milk beverages. Therefore, the objective of the present work was to study the ascorbic acid degradation in a PEF-treated orange juice-milk beverage.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, research and development of new products is leading to the reduction or even displacement of heat treatments and traditional preservatives by treatments capable of assuring the sensory and nutritional properties of the product without reducing food safety. Non-thermal preservation methods are thus of growing interest as alternative treatments, especially highintensity pulsed electric fields (HIPEF), high pressure (HP) and the addition of natural antimicrobial substances (Bendicho, Espachs, Ara´ntegui, & Martı´n, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The initial vitamin C concentration was 103.4 mg/l in the IF preparation. Vitamin C degradation complied with first-order kinetics as expected (Bendicho, Espanchs, Arantegui, & Martin, 2002;Bihel & Birlouez-Aragon, 1998;Burdurlu, Koca, & Karadeniz, 2006;Esteve et al, 1998;Manso, Oliveira, Oliveira, & Frias, 2001) and the first-order rates could be calculated from the slope of the Ln representation. However, above 100°C, the degradation was so fast that very low concentrations, at the limit of the method quantification level, were reached rapidly.…”
Section: Resultsmentioning
confidence: 85%